PENERAPAN TEKNIK SEO (SEARCH ENGINE OPTIMISATION) DENGAN METODE ONPAGE DAN OFFPAGE PADA WEBSITE CARGORIAU.COM - Fauzan Azim (RJOCS (Riau Journal of Computer Science), 2019)
This study aims to determine the application of SEO (Search Engine Optimization) techniques on the cargoriau.com website. This research focuses on the application of marketing by utilizing SEO with onpage and offpage methods in the development and improvement of freight forwarding services, cargo and expeditions in the regency and city areas in Riau Province. The website